Pemberdayaan Umkm Berbasis Kuliner Tradisional Melalui Pelatihan Pembuatan Pempek Khas Palembang pada Masyarakat Kampung Saujana Baru, Malaysia - Khoirul Umam (LPPM Institut Pendidikan Nusantara Global, 2026)
This study is motivated by the potential of Micro, Small, and Medium Enterprises (MSMEs) in the traditional culinary sector in Kampung Saujana Baru, Malaysia, which has not been optimally developed despite its strong economic and cultural opportunities through the utilization of local traditional food. The purpose of this program is to empower the community through training in the production of Palembang’s traditional food, pempek, as an effort to enhance skills, creativity, and the development of culinary-based micro enterprises. The method applied uses an educational, participatory, and hands-on practice approach through several stages, including socialization, demonstration, training, discussion, and evaluation of program outcomes. The results show an increase in community knowledge regarding the history and production process of pempek, improved participant skills in independently producing pempek, and high enthusiasm and active participation throughout the activities. In addition, the program also broadens community awareness of MSME business opportunities in the culinary sector and strengthens social interaction as well as cultural exchange between Indonesia and Malaysia. In conclusion, this empowerment program is proven to be effective in enhancing community capacity in traditional culinary skills while also contributing positively to the development of the creative economy and cross-cultural relations.